2017
DOI: 10.1016/j.jtcvs.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

A derived and validated score to predict prolonged mechanical ventilation in patients undergoing cardiac surgery

Abstract: Prolonged mechanical ventilation after cardiac surgery can be accurately predicted by readily available pre- and intraoperative information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 23 publications
(51 reference statements)
5
55
4
2
Order By: Relevance
“…Several authors have reported outcomes related to prolonged invasive ventilation after cardiac surgery and developed prediction models mainly using 24-, 36-, or 48-hour thresholds for prolonged invasive ventilation. [26][27][28][29][30][31][32][33] The standard definition of prolonged invasive ventilation according the Society of Thoracic Surgeons is a duration exceeding 24 hours. 13 It has been shown that "time to extubation" after cardiac surgery longer than 16 hours predicts poor clinical outcomes (morbidity, mortality, and reintubation) and that liberation from the ventilator within the first 9 hours is a predictor of better postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported outcomes related to prolonged invasive ventilation after cardiac surgery and developed prediction models mainly using 24-, 36-, or 48-hour thresholds for prolonged invasive ventilation. [26][27][28][29][30][31][32][33] The standard definition of prolonged invasive ventilation according the Society of Thoracic Surgeons is a duration exceeding 24 hours. 13 It has been shown that "time to extubation" after cardiac surgery longer than 16 hours predicts poor clinical outcomes (morbidity, mortality, and reintubation) and that liberation from the ventilator within the first 9 hours is a predictor of better postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] One recent large-scale study reported a 7% rate of post-operative ventilation for more than 48 h after cardiac surgery with an inhospital death rate of 22.3%. 9 Circulatory assist devices were though excluded from these studies. Our analysis revealed a 43% rate of PMV among LVAD recipients, which is higher than the rates reported in the general cardiac surgery population.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Previous studies in patients undergoing general cardiac surgery have reported an incidence of 2-10%, with in-hospital mortality rates exceeding 40%. [1][2][3][4][5][6][7][8][9] Previous studies in patients undergoing general cardiac surgery have reported an incidence of 2-10%, with in-hospital mortality rates exceeding 40%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome parameter considered was the duration of postoperative ventilation, which we considered as a surrogate parameter for the severity of critical illness in cardiac surgical patients and is prolonged by PH, RV failure, shock, and prolonged ECC times. [25][26][27]…”
Section: Résumémentioning
confidence: 99%